X-Ray Diffraction of Iron Containing Samples: The Importance of a Suitable Configuration. Issue 6 (3rd July 2018) - Mos, Yvonne M.; Vermeulen, Arnold C.; Buisman, Cees J. N.; Weijma, Jan
ABSTRACT: In X-ray diffraction, a good combination of configuration and sample is essential. Copper radiation for iron containing materials leads to a high background. Although this has been recognized, many researchers still use this combination. To clearly show the unsuitability of copper radiation for iron oxides, magnetite, goethite, maghemite, and hematite were analysed in different configurations using copper or cobalt radiation. Results show effects of fluorescence repressing measures and different radiation sources. Copper radiation diffractograms make phase identification contestable. Studies using copper radiation for iron oxides must therefore be carefully evaluated. Cobalt radiation yielded high quality diffractograms, making phase identification unambiguous.